2018
DOI: 10.1016/j.jaerosci.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the performance of 3 bioaerosol samplers for influenza virus

Abstract: A B S T R A C TRespiratory viral diseases can be spread when a virus-containing particle (droplet) from one individual is aerosolized and subsequently comes into either direct or indirect contact with another individual. Increasing numbers of studies are examining the occupational risk to healthcare workers due to proximity to patients. Selecting the appropriate air sampling method is a critical factor in assuring the analytical performance characteristics of a clinical study. The objective of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 45 publications
0
57
0
Order By: Relevance
“…They suggested the loss of infectivity was due to desiccation or degradation, which could be improved if an enhanced infectivity detection method was incorporated 21 . Two other studies evaluated the collection efficiency of other commercially available air samplers and similarly inferred a loss of infectivity in air samples due to drying of the aerosol particles 22,23 . Despite the inability to recover infectious virus in our air samples, if for aerosol transmission the putative human infectious dose (HID) was 0.6‐3 TCID 50 and equivalent to 90‐1950 RNA copies, 4,8,24 all our PCR‐positive samples exceeded the upper bound of the HID 50 and might indicate the potential to initiate infection via the aerosol route.…”
Section: Discussionmentioning
confidence: 88%
“…They suggested the loss of infectivity was due to desiccation or degradation, which could be improved if an enhanced infectivity detection method was incorporated 21 . Two other studies evaluated the collection efficiency of other commercially available air samplers and similarly inferred a loss of infectivity in air samples due to drying of the aerosol particles 22,23 . Despite the inability to recover infectious virus in our air samples, if for aerosol transmission the putative human infectious dose (HID) was 0.6‐3 TCID 50 and equivalent to 90‐1950 RNA copies, 4,8,24 all our PCR‐positive samples exceeded the upper bound of the HID 50 and might indicate the potential to initiate infection via the aerosol route.…”
Section: Discussionmentioning
confidence: 88%
“…The size distribution of aerosols ( ) is obtained by scanning the voltage that is applied to the DMA. Similar to a previous work ( Li et al, 2018 ), the size-dependent filtration efficiency ( ) is calculated by where and are the size distributions measured at the outlet (downstream) and inlet (upstream) of the filter holder. Based on the size distributions, we can also evaluate the overall number-based filtration efficiencies.…”
Section: Methodsmentioning
confidence: 99%
“…Fabian et al (2009) reported that Teflon and gelatin filters recovered only 22 and 10%, respectively, of infectious influenza viruses compared with the BioSampler. Li et al (2017) evaluated the performance of a 5 ml BioSampler, gelatin filter and glass fibre filter for the collection of influenza H1N1 virus, and found that deactivation of most of the trapped viruses was a result of extraction of virus off the filters. Similarly, relative extraction efficiencies attained using alumina nanofibre vs glass fibre filters were compared for MS2 phage with the BioSampler as a reference sampler by Li et al (2009); the extraction efficiency of the nanofibre filter was less than 10%, while that for the glass fibre filter varied from 32Á3% to 162%.…”
Section: Filtersmentioning
confidence: 99%
“…Li et al . () evaluated the performance of a 5 ml BioSampler, gelatin filter and glass fibre filter for the collection of influenza H1N1 virus, and found that deactivation of most of the trapped viruses was a result of extraction of virus off the filters. Similarly, relative extraction efficiencies attained using alumina nanofibre vs glass fibre filters were compared for MS2 phage with the BioSampler as a reference sampler by Li et al .…”
Section: Samplers For Airborne Virusesmentioning
confidence: 99%